E-GOVERNMENT: PROBLEMS OF PUBLIC ADMINISTRATION (Journal of actual problems of jurisprudence, 2024)
E-government is a single mechanism of interaction between the state and citizens, as well as government agencies, providing partial coordination using information technology.This article will focus on the formation and development of e-government in the modern Republic of Kazakhstan. The relevance of the article lies in the fact that a number of problems in the implementation and application of e-government lies in conducting scientific analysis due to the increased demand for e-government services. The purpose of the study is to determine the nature of the implementation of new e-government technology in the public administration of the Republic of Kazakhstan in comparison with foreign countries, as well as to analyze the current state, trends and problems of e-government development based on the analysis of statistics of the e-government development index and national statistics adopted by the United Nations. According to the results of the study, the work performed by the authors will allow us to analyze and study in detail the problems in the implementation and application of e-government, as well as formulate a priority way to solve them.The topic of e-government development has never lost its relevance: new concepts of the use of ICT in public policy and management have appeared, world and Kazakh empirical data on models and results of e-government functioning in various institutional settings are being updated. The world is rapidly getting better as new technologies penetrate into all areas of our lives. E-government can facilitate citizen participation in public and political life. It provides public access to public information and provides a forum for public discussion that allows citizens to monitor the political decisions of government bodies.Key words: e-government, information and communication technologies, system of state and municipal government, electronic document management, electronic services, e-government.